2012
DOI: 10.1007/s11033-012-1532-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of the microRNA-499 variants with susceptibility to hepatocellular carcinoma in a Chinese population

Abstract: microRNAs (miRNAs) are a new class of small non-coding RNAs that function as tumor suppressors or oncogenes. Single nucleotide polymorphisms (SNPs) in miRNA may contribute to cancer development. We hypothesized that genetic variations of the miRNA could be associated with the risk of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). A total of 100 patients with HCC, 100 cases of chronic hepatitis B and 100 health adults were enrolled in this present study. Two common polymorphisms in pre-miRNAs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 18 publications
3
115
4
Order By: Relevance
“…There were fifteen studies of caucasian descent and twenty-four studies of Asian descent. The genotype distributions in the controls of fourteen studies were not conforming to HWE (p<0.05) (Okubo et al, 2010;Akkiz et al, 2011;Ling et al, 2011;Mittal et al, 2011;Zhou et al, 2011;Xiang et al, 2012;Shan et al, 2013;Vinci et al, 2013;Wei et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Ma et al, 2014;Omrani et al, 2014;Wang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were fifteen studies of caucasian descent and twenty-four studies of Asian descent. The genotype distributions in the controls of fourteen studies were not conforming to HWE (p<0.05) (Okubo et al, 2010;Akkiz et al, 2011;Ling et al, 2011;Mittal et al, 2011;Zhou et al, 2011;Xiang et al, 2012;Shan et al, 2013;Vinci et al, 2013;Wei et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Ma et al, 2014;Omrani et al, 2014;Wang et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…One study was excluded as it was not associated with hsa-mir-499 rs3746444 A>G (Kupcinskas et al, 2012). After further excluding two abstracts (Hu et al, 2009;Hwang et al, 2010), thirty-nine case-control studies involving 14,136 cases and 16,937 controls were selected for meta-analysis (Hu et al, 2009;Tian et al, 2009;Catucci et al, 2010;Liu et al, 2010;Okubo et al, 2010;Srivastava et al, 2010;Akkiz et al, 2011;George et al, 2011;Ling et al, 2011;Mittal et al, 2011;Vinci et al, 2011;Zhou et al, 2011;Alshatwi et al, 2012;Chu et al, 2012;Kim et al, 2012;Min et al, 2012;Xiang et al, 2012;Zhou et al, 2012;Ahn et al, 2013;Lv et al, 2013;Shan et al, 2013;Song et al, 2013;Umar et al, 2013;Vinci et al, 2013;Wei et al, 2013;Wu et al, 2013;Zou and Zhao, 2013;Bansal et al, 2014;Chu et al, 2014;Du et al, 2014;Gutierrez-Camino et al, 2014;Hasani et al, 2014;Hou et al, 2014;Hu et al, 2014;Ma et al, 2014;Omrani et al, 2014;Pu et ...…”
Section: Methodsmentioning
confidence: 99%
“…According to the inclusion criteria, 14 case-control studies (Gao et al, 2009;Chen et al, 2010;Qi et al, 2010;Akkiz et al, 2011a,b,c;Xu et al, 2008Xu et al, , 2011bLiu et al, 2012b;Xiang et al, 2012;Yu et al, 2012;Zhang et al, 2011Zhang et al, , 2012Zhou et al, 2012) were included in this meta-analysis and 134 were excluded. The flow chart of the study selection process is shown in Figure 1.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…Several previous studies indicated that the miR-499A>G polymorphism was associated with susceptibility to hepatocellular carcinogenesis in various populations (Kim et al, 2012;Xiang et al, 2012;Zou and Zhao, 2013;Hu et al, 2013). However, a study conducted in Turkish population reported that the MiR-499A>G polymorphism did not have any major role in genetic susceptibility to hepatocellular carcinogenesis (Akkiz et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…It was reported that two common miRNA, miR-149C>T and miR-499A>G, are associated with various cancers, such as esophageal cancer, cervical cancer and prostate cancer (He et al, 2012). Moreover, a recent meta-analysis reported that the miR-149C>T polymorphism is associated with susceptibility to hepatitis B virus-related HCC in the Chinese population (Xu et al, 2013), and two case-control studies indicated that miR-499A>G variants were associated with susceptibility to HCC (Xiang et al, 2012;Hu et al, 2013). However, few studies have evaluated the interaction between miR-149C>T and miR-499A>G and HBV infection.…”
Section: Introductionmentioning
confidence: 99%